Persepsi Gereja Masehi Advent Hari Ketujuh tentang Penggunaan Alat Musik Perkusi dalam Kebaktian Gereja Berdasarkan Mazmur 81:3 - Rafael Natanael; Milton T. Pardosi (Departement of Mathematics Education, 2023)
Since ancient times, music has been a part of human life. Music has also been used in worship and religious ceremonies, just as the Israelites did in the Old Testament. To this day, music continues to be used for the purposes of worship. The Adventist Church has both pros and cons regarding the use of percussion instruments in worship. Various opinions have been expressed regarding the use of musical instruments in worship, particularly percussion instruments in worship in the Seventh-day Adventist Church. The purpose of this research is to understand the perceptions of members of the Seventh-day Adventist Church regarding the use of percussion instruments in church worship. By doing so, it can increase understanding and awareness among members of the Seventh-day Adventist Church so that they can practice good use of musical instruments in worship. This research uses a qualitative method, which involves collecting data from books, research journals, literature, online media, and the Bible that are relevant to the material being discussed. The results show that some researchers agree with the use of percussion instruments in worship as long as they are used properly and do not distract from focusing on God. Those who oppose it see percussion as worldly music that is not suitable for worship because it can disrupt the solemnity. Percussion is not specifically described in theological terms as being prohibited, but the Adventist Church has provided guidelines for the proper use of musical instruments in worship. Therefore, it can be concluded that the use of percussion music must be carefully and wisely considered, in accordance with biblical teachings and the Adventist Church.